The effectiveness of community friendship groups on participant social and mental health: a meta-analysis - Grishina, Micah; Rooney, Rosanna Mary; Millar, Lynne; Mann, Rachel; Mancini, Vincent Oreste (Frontiers in Psychology, 2023)
This meta-analysis investigated whether structured or unstructured community friendship groups are more effective for mental health and social capital outcomes. A systematic search of quantitative studies was conducted across seven databases and study quality was assessed using the Effective Public Health Practice Project (EPHPP) tool. Eight studies (2 unstructured and 6 structured friendship groups) were included in the review, published between 2005 and 2020. A meta-analysis was conducted for the mental health outcome of depression which supported structured friendship groups having a small effect on participant depression symptoms. There was substantial heterogeneity between studies to calculate pooled effect sizes for any social capital outcomes. Data synthesis indicated mixed reviews for social capital outcomes, likely due the large heterogeneity and limited studies. Overall this meta-analysis provides limited support for positive mental health outcomes following community-based friendship group interventions. There is a need for additional research as a large research gap remains particularly for unstructured friendship groups.